2018
DOI: 10.1536/ihj.17-026
|View full text |Cite
|
Sign up to set email alerts
|

Combining Percutaneous Ultrasound-Guided Hematoma Aspiration and Compression Repair to Treat Femoral Artery Pseudoaneurysm after Cardiac Catheterization

Abstract: This study aimed to prospectively evaluate the safety and efficacy of a new developed method that uses percutaneous ultrasound-guided hematoma aspiration followed by targeted localized manual compression for treatment of femoral artery pseudoaneurysm after cardiac catheterization, which obviates thrombin use, surgery, and long-time compression.From January 2007 to July 2014, 32 patients (17 women; mean age, 55.3 ± 11.5 years) out of 8,725 consecutive cases undergoing cardiac catheterization via femoral access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…The mechanism of injury, in this case, is related to direct trauma to the arterial wall during the procedure, as well as underlying arterial disease and coagulopathy. Puncture sites have varying degrees of associated risk related to PSA formation, with femoral access procuring less risk than brachial access [ 1 , 2 ]. Manual compression has also been found to decrease the risk of PSA formation [ 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of injury, in this case, is related to direct trauma to the arterial wall during the procedure, as well as underlying arterial disease and coagulopathy. Puncture sites have varying degrees of associated risk related to PSA formation, with femoral access procuring less risk than brachial access [ 1 , 2 ]. Manual compression has also been found to decrease the risk of PSA formation [ 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT angiography may also be used as an imaging modality, as it provides more information on the anatomy of the affected area [ 8 ]. Treatment options include conservative management, compression therapy, thrombin injection, or surgical intervention, depending on the size and location of the PSA [ 1 , 7 , 9 ]. Ultrasound-guided compression repair and thrombin injection are preferred treatment options for non-complicated PSAs; however, surgical intervention is indicated in PSAs that are infected, progressively growing, compressing underlying structures, or causing skin necrosis [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jalaeian et al 9 reported one patient who was on long‐term hemodialysis who died due to an anaphylactic reaction to bovine thrombin. Although some studies reported the use of autologous thrombin or recombinant human thrombin to treat pseudoaneurysms in an effort to reduce the risk of anaphylaxis, Chen et al 10 reported this treatment did not reduce the risk of arterial thrombosis and was also expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Ancak bu çalışmada hastaların yaşının nispeten genç olması, psödoanevrizma kesesinin tek odacıklı olması gibi kısıtlamalardan bahsedilmiştir. Ayrıca daha yüksek vücut kitle indeksi olan hastalarda aspirasyon ve kompresyonun yetersiz olabileceği belirtilmiştir (23).…”
Section: Discussionunclassified